Analisis Pengambilan Keputusan Perubahan Konversi Tambak Ikan Ke Kebun Kelapa Sawit Di Desa Kasano Mamuju Utara - Nasir, Akbar; Maryono, Maryono (Nekton, 2021)
This study aims to determine the causes and impacts of the conversion of fish ponds into oil palm plantations in Kasano Village, North Mamuju. This study uses a qualitative method with a descriptive research approach. Data collection used observation techniques and direct interviews with fishermen who converted their ponds into oil palm plantations in Kasanao Village, Baras District, North Mamuju Regency. The results of this study indicate that the number of fishermen who convert their ponds to oil palm plantations is around 80%. Land conversion occurs gradually, there is no change in social status due to land conversion. Instead, the conversion of the ponds is due to the problem of the value of oil palm being higher than milkfish or shrimp.